MODULO CONCEPT IN DETERMINING RICE PLANTING TIME IN KASEPUHAN CISUNGSANG: AN ETHNOMATHEMATICS STUDY - Alamsyah, Trian Pamungkas; Nirmalasari, Dinar; Rafianti, Isna (Wilangan: Jurnal Inovasi dan Riset Pendidikan Matematika, 2025)
This study aims to examine the application of the mathematical concept of modulo in determining the rice planting period among the indigenous people of Kasepuhan Cisungsang. Using an ethnomathematical and qualitative approach, the study found that the community classifies dates in the Hijri calendar based on the remainder when divided by four (modulo 4). Dates with remainders of 1, 2, and 3 are considered auspicious for planting, while those with a remainder of 0 (multiples of 4) are avoided due to cultural beliefs. Although this practice is not formally recognized as mathematics, it demonstrates a mathematical reasoning embedded within local traditions. The findings emphasize that ethnomathematics serves as a bridge between formal mathematical concepts and local culture and can enhance contextual mathematics learning in schools.